Rendering life molecular models, modelers, and excitable matter - Myers, Natasha 1974- (Duke University Press, 2015)
Crystallographic renderings -- Tangible media -- Molecular embodiments -- Rending representation -- Remodeling objectivity -- Machinic life -- Lively machines -- Molecular calisthenics -- Conclusion: what is life becoming? -- Appendix: a protein primer
Includes bibliographical references and index. - Description based on print version record
Keywords: Proteins / Structure; Molecules / Models; X-ray crystallography; Molecular biologists; Molekularbiologie